THE INFLUENCE OF TAX KNOWLEDGE, TAX SOCIALIZATION, AND TAX SANCTIONS ON TAX COMPLIANCE OF MSME ACTORS WITH TAX SERVICE QUALITY AS A MODERATING VARIABLE - Geraldi Hartanto (Publikasi Indonesia, 2025)
Tax compliance among Micro, Small, and Medium Enterprises (MSMEs) is critical for Indonesia’s revenue stability, yet challenges persist due to low awareness and complex procedures. This study investigates how tax knowledge, socialization, and sanctions influence compliance, with tax services as a moderating variable. Using a quantitative approach, data were collected via online questionnaires from 73 MSME taxpayers in Jakarta and analyzed through PLS-SEM to test direct and moderated relationships. Results indicate that tax knowledge, socialization, and sanctions significantly affect compliance, with tax services enhancing these relationships. Respondents positively rated tax authorities’ communication and digital services, though perceptions of sanctions varied. The findings highlight the importance of tailored taxpayer education and user-friendly digital services to improve compliance. This research contributes to the literature by empirically validating the moderating role of tax services and offering policymakers strategies to optimize MSME compliance through equitable policies and digital tools. Implications suggest expanding demographic analyses and leveraging behavioral economics for future studies.